Effects of Water Addition on Reproductive Allocation of Dominant Plant Species in Inner Mongolia Steppe - Liu, Yongjie; Li, Zhenqing (Frontiers in Plant Science, 2020)
Extreme events such as extreme drought and precipitation are expected to increase in intensity and/or duration in the face of climate change. Such changes significantly affect plant productivity and the biomass allocation between reproductive and vegetation organs (i.e. reproductive allocation). Our aims are to test the effects of water addition on the trade-offs in allocation of plant biomass and whether such effects are modified by species. A manipulative experiment was conducted from May 2000 to October 2001, where four dominant plant species (i.e. Leymus chinensis, Stipa grandis, Artemisia frigida and Potentilla acaulis) in Inner Mongolia steppe in China were treated with 8 levels of water additions. Results demonstrated that water addition significantly affected the reproductive allocation of plants, and such effects were modified by species. Specially, with increasing water availability, L. chinensis was not impacted, while A. frigida allocated more biomass to reproductive organs than to vegetative organs, while such allocation of S. grandis and P. acaulis firstly decreased, and then increased after reaching a peak. Our results indicated that plant species can adjust their reproductive allocation patterns to deal with water availability gradients. Climatic factors such as rainfall and temperature usually co-appearing, thus future research should explore the jointed effects of several climate change factors on grasslands in order to maintain the healthy and sustainable of grasslands.